Abundance and distribution of microplastics in the surface sediments from the northern Bering and Chukchi Seas. (February 2019) - Mu, Jingli; Qu, Ling; Jin, Fei; Zhang, Shoufeng; Fang, Chao; Ma, Xindong; Zhang, Weiwei; Huo, Cheng; Cong, Yi; Wang, Juying
Abstract: Worldwide the seafloor has been recognized as a major sink for microplastics. However, currently nothing is known about the sediment microplastic pollution in the North Pacific sector of the Arctic Ocean. Here, we present the first record of microplastic contamination in the surface sediment from the northern Bering and Chukchi Seas. The microplastics were extracted by the density separation method from collected samples. Each particle was identified using the microscopic Fourier transform infrared spectroscopy (μFTIR). The abundances of microplastics in sediments from all sites ranged from not detected (ND) to 68.78 items/kg dry weight (DW) of sediment. The highest level of microplastic contamination in the sediment was detected from the Chukchi Sea. A negative correlation between microplastic abundance and water depth was observed. Polypropylene (PP) accounted for the largest proportion (51.5%) of the identified microplastic particles, followed by polyethylene terephthalate (PET) (35.2%) and rayon (13.3%). Fibers constituted the most common shape of plastic particles. The range of polymer types, physical shapes and spatial distribution characteristics of the microplastics suggest that water masses from the Pacific and local coastal inputs are possible sources for the microplastics found in the study area. In overall, our results highlight the global distribution of these anthropogenic pollutants and the importance of management action to reduce marine debris worldwide. Graphical abstract: Highlights: This is the first report of MPs in sediments from the Bering-Chukchi Sea shelf. MPs levels were lower than those found in other regions of the world. The sediments from the Chukchi Sea possessed the highest MPs abundances. Fibers constituted the most common type in the Arctic sediments.